Topical 5-fluorouracil treatment of vaginal intraepithelial neoplasia - Caglar, H; Hertzog, R W; Hreshchyshyn, M M (Obstetrics and gynecology (New York. 1953), 1981)
In a prospective study, 27 patients with intraepithelial vaginal neoplasia diagnosed by colposcopically directed biopsies were treated with topical 5-fluorouracil. The cream was applied daily to the entire vagina until mucosal irritation occurred (5 to 10 days). Courses were repeated every 2 weeks for a total of 2 to 3 courses, which were considered 1 treatment, before response was evaluated. Those found to have persistent neoplasia as designated by positive vaginal cytology and/or colposcopically directed biopsies received a second 3-course treatment and were evaluated again. Except for 2 patients (1 who died from intercurrent disease during the treatment and another, evaluated prematurely after the first course of therapy, who was found to have persistent disease and was treated by other means), all patients responded with complete regression of vaginal intraepithelial neoplasia. Three patients developed reactivation of disease within 1 year, were retreated, and are currently completely free of disease. The authors believe the results of this study are very encouraging.